Development of the measurement of radium using a germanium detector with molecular recognition resin. (27th September 2018) - Ito, S; Ichimura, K; Takaku, Y; Abe, K; Ikeda, M; Kishimoto, Y
Abstract: High-purity germanium (HPGe) detectors are widely used for the measurement of low concentrations of radioactivity. For the Super-Kamiokande Gadolinium project, the concentration of radium in Gd$_2$ (SO$_4$ )$_3{·}$ 8H$_2$ O is determined by using HPGe detectors. The amount of the sample is generally limited by the size of the sample space of an HPGe detector. This leads to limitation of the detector efficiency. A new method of chemical extraction using molecular recognition resin was developed to minimize this problem. Using the developed method, radium could be extracted from Gd$_2$ (SO$_4$ )$_3{·}$ 8H$_2$ O and concentrated to a smaller amount of the resin at a recovery rate of 81%$±$ 4%, which was estimated by using barium as a recovery monitor. This made it possible to set the sample closer to an HPGe crystal and reduce the self-screening effect, resulting in increased detection efficiency for an HPGe detector. The method developed is reported in this letter.